Bridging Basic and Clinical Research in Early Life Adversity, DNA Methylation, and Major Depressive Disorder - Brown, Amanda; Fiori, Laura M.; Turecki, Gustavo (Frontiers in Genetics, 2019)
Early life adversity (ELA)- including childhood physical, emotional, and sexual abuse, as well as childhood neglect- is an important predictive factor for negative psychopathology, including Major Depressive Disorder (MDD). ELA can epigenetically regulate key emotional and behavioral systems in ways that can stably persist into adulthood and contribute to the development of MDD and other psychopathology. DNA methylation has been one of the most investigated forms of epigenetic regulation in ELA to MDD pathway. From these studies, genes and sites associated with ELA/MDD have been identified and should be further investigated in order to identify potential avenues for intervention.